Lexicographic goal programming approach for a short-term mining planning problem. Issue 2 (1st February 2023) - Martins, Aldrin Gustavo; Souza, Marcone Jamilson Freitas
Abstract : This article addresses a short-term mining planning problem. There are four objectives to be minimized: the deviations in grades and ore proportion in particle size ranges of the plant goals, the deviation in the waste mass to achieve the stripping rate, and the number of truck trips between mining fronts and discharges. The problem was solved through the lexicographical goal programming (LGP) method, which generates solutions that can guarantee a more comprehensive analysis of the decision-making process. The LGP method was tested by using several scenarios of a Brazilian mining company. These scenarios differ in the number of excavators and the tolerances concerning meeting the plants' ore grades. In the results, the impact on the values of the other objectives is analysed of varying the number of excavators and the tolerances in the plants' grade targets.